﻿Four new species of Diaporthe (Diaporthaceae, Diaporthales) from forest plants in China - Lingxue Cao; Dun Luo; Wu Lin; Qin Yang; Xiaojun Deng (MycoKeys, 2022)
Species of Diaporthe inhabit a wide range of plant hosts as plant pathogens, endophytes and saprobes. During trips to collect forest pathogens in Beijing, Jiangxi, Shaanxi and Zhejiang Provinces in China, 16 isolates of Diaporthe were obtained from branch cankers and leaf spots. These isolates were studied by applying a polyphasic approach including morphological, cultural data, and phylogenetic analyses of the nuclear ribosomal internal transcribed spacer (ITS), calmodulin (cal), histone H3 (his3), partial translation elongation factor-1α (tef-1α) and β-tubulin (tub2) loci. Results revealed four new taxa, D. celticola, D. meliae, D. quercicola, D. rhodomyrti spp. nov. and two known species, D. eres and D. multiguttulata.